(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2025)
The popular legislative initiative serves as a complementary mechanism of citizen participation within the framework of representative democracy, intended to strengthen the relationship between government and citizens by enabling the submission of proposals for laws or decrees. Nevertheless, its implementation at the federal level in Mexico continues to face significant obstacles: the legal requirements are burdensome, the effective influence of individuals on the legislative process remains limited, and its practical use has been minimal more than a decade after its incorporation into the Constitution. This study examines the legal structure of this mechanism and offers an empirical assessment based on data concerning initiatives submitted to the Houses of Congress.